Muslimah Hybrid Identity in Amulya Malladi’s The Sound of Language - Seshu, Bandaru S.S.S.S.K. (Muslim English Literature, 2023)
This study analyses Amulya Malladi’s novel The Sound of Language using a postcolonial and Islamic feminist approach. The paper explores how the novel reflects identity, Otherness, the imperial situation, and the experience of alienation in the diaspora. In The Sound of Language, the author portrays the main character's life in the Muslim diaspora. It depicts the subject's journey towards a multicultural identity and her mission to understand who she is and where she fits in the global community. This study examines how a Muslim subject develops their identity in a postcolonial European setting and analyses the problems raised by how the writer presents the character in the book. This research especially explores Malladi's identity-making process, engaging with concepts of Ngugi wa Thiongo's Language and Identity, Homi K. Bhabha's Hybridity, and Fatima Mernissi's Muslim women's liberation. In addition, this investigates how the author explores the connection between language acquisition and identity formation, examining how natives influence non-natives and the extent of Danish society's acceptance of Afghan culture and languages. The study reveals that Muslim characters in occidental societies, like Raihana does when she moves to Denmark, will develop a hybrid identity that incorporates both her Muslim background and the contemporary free-thinking society of the West. This article presents two subsections of a study: the Postcolonial and the Islamic feminist approaches. Both sections explain how Raihana formed her hybrid identity as a Muslim woman in a European country.